2011
DOI: 10.2106/jbjs.i.01713
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Intimate Partner Violence across Orthopaedic Fracture Clinics in Ontario

Abstract: our study suggests a high prevalence of intimate partner violence among female patients with injuries who presented to two orthopaedic fracture clinics in Ontario. Surgeons and health-care personnel in fracture clinics should consider intimate partner violence when interacting with injured women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…One can quibble over the details of the paper-the response rate, for example, was somewhat low-but the data fit in very well with some previous publications on the subject [3,4].…”
supporting
confidence: 73%
“…One can quibble over the details of the paper-the response rate, for example, was somewhat low-but the data fit in very well with some previous publications on the subject [3,4].…”
supporting
confidence: 73%
“…For example, several American, Australian, and Canadian studies have found that IPV prevalence is well over 10% in both emergency medicine 16-20 and family medicine. 21-25 In addition, the PRAISE Investigators 26 recently found that the 12 month prevalence of IPV in orthopaedic fracture clinics, one of the most common specialties among our respondents, was over 30%.…”
Section: Discussionmentioning
confidence: 61%
“…This is likely a gross misperception. A recent study examining the prevalence of IPV in orthopaedic fracture clinics found a 12-month prevalence rate of 17.8% across North American centers [4]. Respondents also were uncomfortable with identifying and treating victims of IPV and believed that multiple barriers existed for effective identification and assistance of victims.…”
Section: Discussionmentioning
confidence: 99%